Apneustic breathing provoked by limbic influences. Issue 851 (September 1996) - Stewart, J.; Howard, R. S.; Rudd, A. G.; Woolf, C.; Russell, R. W.
Abstract : We describe a 64-year-old man with cerebrovascular disease who had an acute stroke characterised by pseudobulbar palsy, facial weakness, and pyramidal signs. He developed frequent emotional outbursts followed by periods of apneusis. Between these episodes he breathed with a regular and unvarying rate and tidal volume. Autopsy showed extensive cortical, subcortical and pontine infarction. The respiratory pattern indicated a dissociation between voluntary and automatic pathways. The descending limbic pathways were preserved but an abnormal pattern of automatic breathing (ie, apneusis) occurred because of the presence of bilateral pontine infarction.